Iron-Catalyzed Diastereoselective Synthesis of Disubstituted Morpholines via C–O or C–N Bond Formation - Aubineau, Thomas; Dupas, Alexandre; Zeng, Tian; Cossy, Janine (Synlett, 2021)
The diastereoselective synthesis of 2,6- and 3,5-disubstituted morpholines was achieved from 1,2-amino ethers and 1,2-hydroxy amines substituted by an allylic alcohol using an iron(III) catalyst. The morpholines were obtained either by C–O or C–N bond formation. A plausible mechanism is suggested, involving a thermodynamic equilibrium to explain the formation of the cis diastereoisomer as the major product.
Keywords: morpholine; iron; diastereoselective; thermodynamic equilibrium